Unveiling polish judges’ views on empathy and impartiality - Stępień, Mateusz (Frontiers in Sociology, 2024)
The exploration of empathy’s significance in judicial decision-making has garnered attention in scholarly discourse, yet there is a noticeable gap in studies delving into judges’ perceptions of empathy’s role, advantages, and impediments. This neglect reflects an “anti-empathetic” discourse that overlooks the insights of those central to justice delivery. Consequently, there is an urgent need for empirical inquiries into judges’ perspectives on empathy, its definition, and its integration into their work. Primarily concentrated in Anglo-Saxon jurisdictions, empathy research in judicial decision-making lacks diversity. This paper responds to two critical calls: understanding judges’ views on empathy and expanding research beyond common-law systems. It presents empirical research investigating Polish judges’ perspectives on empathy, with a focus on its relationship with impartiality. This inquiry is crucial given debates on whether empathy compromises impartiality, particularly evident in discussions surrounding judicial appointments. Based on in-depth interviews with Polish judges, this article identifies five strategies employed by judges to reconcile empathy with impartiality, termed as “paths”: (1) claiming symmetry in distributing empathy between parties, (2) defining empathy as unemotional, (3) mitigating empathy’s influence on judgments, (4) emphasizing control over empathy, and (5) deabsolutizing formal impartiality and making more room for empathy. The paper discusses these strategies and comments on them, shedding light on the nuanced ways in which judges navigate the intersection of empathy and impartiality in their decision-making processes.